Can Smart Governance Works in Traditional Indigenous Markets? - Denny Andriana (Universitas Padjadjaran, 2023)
One of the underlying characteristics of a “smart governance” notion is responsive government. The public expects the government to be its receptive partner. However, prior research has indicated that a growing lack of public trust in government is a common phenomenon in most developing countries; thus, expecting a responsive government is difficult. This paper aims to determine whether smart governance works in traditional indigenous markets, known as pasar, in Indonesia. The study employs a qualitative case-study method. A semi-structured interview of pasar key informants gathered empirical evidence for the case study. The findings indicate that the bureaucratic culture, via the role of supervisory boards, in Pasar has restrained the managers’ responsiveness to public demands. Consequently, complaints that surface in Pasar cannot be solved immediately. In conclusion, it can be said that they cannot implement smart governance in Pasar.